2009
DOI: 10.1016/j.jhydrol.2009.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Controls on the spatial and temporal variability of 222Rn in riparian groundwater in a lowland Chalk catchment

Abstract: Radon is a powerful tracer of stream-aquifer interactions. However, it is important to consider the source and behaviour of radon in groundwater when interpreting observations of river radon in relation to groundwater discharge. Here we characterise the variability in groundwater radon concentrations in the riparian zone of a Chalk catchment. Groundwater 222 Rn (radon) concentrations were determined in riparian zone boreholes at two sites in the Lambourn catchment, Berkshire, UK, over a two year period. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…Finally, in rivers that run through coarse alluvial sediments, water from the hyporheic or parafluvial zones may provide a source of additional 222 Rn to groundwater inflow (Cook et al, 2006;Cartwright et al, 2014;Bourke et al, 2014a). As has been outlined in several studies, comparison of the calculated groundwater inflows from 222 Rn with those made from other geochemical tracers or with streamflow measurements is a crucial test of the calculations (Cook et al, 2003(Cook et al, , 2006Mullinger et al, 2007Mullinger et al, , 2009Cartwright et al, 2011Cartwright et al, , 2014McCallum et al, 2012;Unland et al, 2013). Carrying out studies at baseflow conditions when most of the water contributing to the streams is from groundwater inflows allows for a comparison between the calculated groundwater inflows and the observed increase in streamflows, which in turn provides for a test of the parameters used in the 222 Rn mass balance (Cartwright et al, 2014).…”
Section: Rn As a Tracer Of Groundwater Inflowsmentioning
confidence: 98%
“…Finally, in rivers that run through coarse alluvial sediments, water from the hyporheic or parafluvial zones may provide a source of additional 222 Rn to groundwater inflow (Cook et al, 2006;Cartwright et al, 2014;Bourke et al, 2014a). As has been outlined in several studies, comparison of the calculated groundwater inflows from 222 Rn with those made from other geochemical tracers or with streamflow measurements is a crucial test of the calculations (Cook et al, 2003(Cook et al, , 2006Mullinger et al, 2007Mullinger et al, , 2009Cartwright et al, 2011Cartwright et al, , 2014McCallum et al, 2012;Unland et al, 2013). Carrying out studies at baseflow conditions when most of the water contributing to the streams is from groundwater inflows allows for a comparison between the calculated groundwater inflows and the observed increase in streamflows, which in turn provides for a test of the parameters used in the 222 Rn mass balance (Cartwright et al, 2014).…”
Section: Rn As a Tracer Of Groundwater Inflowsmentioning
confidence: 98%
“…The average concentrations range from 0.3 to 76.9 Bq/L; the arithmetic mean is 12.8 Bq/L; the median of the distribution is 5.3 Bq/L; and the standard deviation is 17.7 Bq/L. Several studies related to the use of radon as a hydrogeochemical tracer can be found in the literature, [7,34,35]. The main factors that influence the presence of 222 Rn in groundwater are the content of 226 Ra in the reservoir rock and its emanation coefficient, as well as the feasibility of mixing of various groundwater components [36,37].…”
Section: Radon As a Natural Radioactive Tracer To Study Aquifer Systemsmentioning
confidence: 99%
“…Geochemical tracers including major ions, stable isotopes and radiogenic isotopes have been used to estimate groundwater fluxes in gaining rivers (Cartwright et al, 2008(Cartwright et al, , 2010Cook, 2012;Cook et al, 2003Cook et al, , 2006Durand et al, 1993;Genereux et al, 1993;Genereux and Hemond, 1990;Lamontagne et al, 2005Lamontagne et al, , 2008Lamontagne and Cook, 2007;Mullinger et al, 2007Mullinger et al, , 2009Négrel et al, 2003;Rhode, 1981;Ribolzi et al, 2000;Stellato et al, 2008). The utility of each of these tracers depends on a variety of factors including the difference between the concentration of the tracer in groundwater compared to surface water, its spatial and temporal variability, the accurate characterisation of its sources and sinks, and the potential for it to change by processes such as evaporation, precipitation, radioactive decay, degassing, or biogeochemical reactions.…”
Section: N P Unland Et Al: Investigating the Spatio-temporal Variamentioning
confidence: 99%
“…Cook, 2012;Cook et al, 2006). The use of 222 Rn as a groundwater tracer has increased over the last two decades as methods for its measurement in the field have improved Cartwright et al, 2011;Cook et al, 2003;Ellins et al, 1990;Genereux and Hemond, 1990;Gilfedder et al, 2012;Hofmann et al, 2011;Mullinger et al, 2007Mullinger et al, , 2009Santos and Eyre, 2011). The short half-life (3.82 days) and degassing of 222 Rn from surface water makes it a particularly valuable groundwater tracer, as elevated 222 Rn activities will only occur close to zones of groundwater discharge.…”
Section: N P Unland Et Al: Investigating the Spatio-temporal Variamentioning
confidence: 99%